Survey of Newcastle Disease Effects on Broiler Breeder Performance - Feizi, Adel; Nazeri, Mehrdad (International Journal of Poultry Science, 2011)
Newcastle disease is a serious and commonly fatal disease of chickens caused by a Paramyxovirus. Other avian species are also infected, but usually with less severe consequences. In most developing countries Newcastle disease is the most important infectious disease affecting village chickens. The usual source of infection for village chickens is usually other chickens. The role of other birds as carriers to initiate outbreaks in villages is not well documented. Both epidemic and endemic forms of Newcastle disease occur in village conditions. The aim of this study was to assess the effect of Newcastle disease on broiler breeder performance. In this study, four ND afflicted broiler breeder flocks were selected and the effect of this disease was appraised on these flocks. Of cases studied can be refer the mortality rate, production loss, clinical signs, necropsy signs and disease period. Also in afflicted flocks blood sampling was taken in early and 14 days after of involvement to recording the antibody titer by HI test. Of each saloon number of 16 samples was taken. Samples were referred to lab immediately. In lab, HI test was carried out and antibody titer of ND was measured. It must be noted that race of all flocks was Ross. After sampling from chicks on mentioned days were used of HI method for measurement of serum antibody titer. In this study revealed that antibody titer in before and after N.D has significant difference (p